2015
DOI: 10.1210/en.2014-1611
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Induces Resistance to the Anorectic Effect of Hypothalamic Malonyl-CoA and the Thermogenic Effect of Hypothalamic AMPK Inhibition in Female Rats

Abstract: During gestation, hyperphagia is necessary to cope with the metabolic demands of embryonic development. There were three main aims of this study: Firstly, to investigate the effect of pregnancy on hypothalamic fatty acid metabolism, a key pathway for the regulation of energy balance; secondly, to study whether pregnancy induces resistance to the anorectic effect of fatty acid synthase (FAS) inhibition and accumulation of malonyl-coenzyme A (CoA) in the hypothalamus; and, thirdly, to study whether changes in hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 64 publications
4
74
0
Order By: Relevance
“…Of note, this mechanism is shared by E2, which also displays a potent central thermogenic action (Martínez de Morentin et al., 2014, Martínez de Morentin et al., 2015). Here we show that male rats did not respond to central BMP8B administration, which might indicate dependence on ovarian steroids, a possibility that was further confirmed by using OVX rats with and without E2 replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this mechanism is shared by E2, which also displays a potent central thermogenic action (Martínez de Morentin et al., 2014, Martínez de Morentin et al., 2015). Here we show that male rats did not respond to central BMP8B administration, which might indicate dependence on ovarian steroids, a possibility that was further confirmed by using OVX rats with and without E2 replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an adenovirus‐mediated activation of AMPK in the VMH (but not in the ARC) prevented the increase in BAT thermogenesis activity and body weight loss associated induced by centrally administrated E2 . Interestingly, variations in E2 levels during the oestrous cycle and pregnancy were also described to modulate the AMPK pathway, supporting also its physiological importance . Recent studies have demonstrated that bone morphogenetic protein 8B (BMP8B) acts centrally on the modulation of BAT thermogenic activity depending on the activation status of AMPK in the VMH.…”
Section: Hypothalamic Ampk and Thermogenesismentioning
confidence: 94%
“…The physiological relevance of these findings is given by the fact that this integrative mechanism is not limited to THs. Indeed, it was demonstrated that the central action of E2, through its binding to oestrogen receptor alpha (ERα), decreased AMPK activity selectively in the VMH, inducing an increase in BAT thermogenic capacity through the SNS in a feeding‐independent manner . Moreover, an adenovirus‐mediated activation of AMPK in the VMH (but not in the ARC) prevented the increase in BAT thermogenesis activity and body weight loss associated induced by centrally administrated E2 .…”
Section: Hypothalamic Ampk and Thermogenesismentioning
confidence: 99%
“…Hypothalamic accumulation of malonyl-CoA after pharmacological or genetic manipulation of key enzymes such as fatty acid synthase, acetyl-CoA carboxylase, and malonyl-CoA decarboxylase promotes downregulation of AgRP/NPY and upregulation of CART/POMC expression, eliciting anorexia [101][102][103][104][105][106][107][108][109] . The metabolic relevance of these enzymes goes beyond the control of feeding, because it has been demonstrated that the surplus of hypothalamic long-chain fatty acid-CoA also impacts peripheral glucose and energy homeostasis through a leptin-independent effect [110][111][112] .…”
Section: From Hypothalamic Lipid Metabolism To Whole Body Energy Homementioning
confidence: 99%